Selected acute phase proteins, oxidative stress biomarkers, and antioxidants in aborting and non-aborting goats infected with Border disease virus - Balikci, Engin; Yildiz, Atilla; Gurdogan, Fuat (Natl Veterinary Research Inst, 2013)
Goats were grouped into three health categories based on the clinically and serologically proven cases: infected non-aborting (group A) (n = 10), infected aborting (group B) (n = 10), and non-infected (group C) (n = 10). In all groups, blood samples were collected and analysed for malondialdehyde (MDA) and nitric oxide (NO) levels in plasma, haptoglobin (Hp) and amyloid A (SAA) in serum, and superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities in erythrocytes. A statistically significant decrease in GSH-Px and SOD activities and increase in MDA, NO, Hp, and SAA levels were observed in groups A and B compared to group C. Additionally, MDA, NO, Hp, and SAA levels of the aborting goats were significantly higher, whereas SOD levels were lower than those of the non-aborting groups.
Keywords: goat; border disease; acute phase proteins; oxidative stress; abortion